The Dual Role Of Women Farm Workers In Payung Village, Payung District, South Bangka Regency - Boli Hariyanto; Fitri Ramadhani Harahap; Tiara Ramadhani (Profesional Muda Cendekia Publishing, 2023)
This research aimed to describe the dual roles of working women is unavoidable nowadays, as the practice by women farmworker's in Payung Village, they carry out their activities in domestic and public spheres, apart from having a role in household affairs, they also work outside the home. The purpose of this research is to find out the form of the dual roles of women farmworkers, and what factors that encourage women to work as farmworkers, how the impact of this dual roles on women farmworkers. This research using descriptive qualitative approach. The sources of research data come from primary and secondary data. Primary data is obtained through observation and interviews with women farmworkers, the husbands, and also land owners. Secondary data is obtained through documentation and library research. The technique for determining informants used purposive sampling technique. The theory to analyze the phenomenon in this research is the theory of liberal feminism by MaryWollstonecraft. The results of the research show the dual roles of women farmworkers is the role of a housewife that caring to household affairs, and have a social role in group or community. Then the factors that encourage women to work as farmworkers are because they should complete family needs, low education levels, and salaries. Meanwhile, the impacts including the positive and negative. The positive impact is that women farmworkers can increase their independence to earn income and their time for socializing. The negative impact is declining health conditions due to work and also feeling guilty.